EMPOWERING MEDAN ART COMMUNITY THROUGH DEVELOPING GRAFFITY WRITING AS CREATIVE INDUSTRY MODEL (THE LOCAL WISDOM OF MALAY DELI) - Juliana Juliana; Fatimah Fatimah; Aprili Yanti (Universitas Islam Sumatera Utara (UISU), 2018)
This paper promotes a concept to empower Medan art community through the development of writing graffiti as a media of creative industry entrepreneurs based the local wisdom with reintroducing and as well as maintaing the local wisdom of the Pantuns of Malay Deli. The method of this paper is an ethnographic method, using a qualitative descriptive approach. The data on this paper are obtained using observation and interview. The analysis of this paper are: (1) The pantuns of Malay Deli that have the local wisdom values of cultural behaviors for general public environment which consists of cleanliness, security, orderliness, beauty and kinship values. And (2) the iconic character of Mr. Belalang as a characteristic figure in the Malay story as an icon to introduce, inspire and form the distinctive personality as well as embody the instilling of high cultural values for the culture of the terrain community. The result of this paper are that (1) Marchandise or sourvenirs using the pantun of Malay Deli with the icon of Mr. Belalang as a form of creative industry based on local wisdom of Malay deli culture, (2) The place of graffiti writing as a media for developing Medan art community in expressing creativity based on local wisdom of Malay Deli. Briefly, the model of graffiti writing as a media for empowering Medan art Community in reintroducing and maintaining the culture of Malay Deli which are applied effectively as the form of creative industry entrepreneurs based the local wisdom.